The Influence Of Spa Therapy And Diabetic Foot Exercise On Diabetic Peripheral Neuropathy Patients - SUYANTO SUYANTO (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2017)
Diabetic peripheral neuropathy patients with decreasing in foot sensation will impact on diabetic ulcers.  This study aims to explore the effect of combination between diabetic legs exercise and SPA therapy on foot sensitivity escalation among patients with diabetic peripheral neuropathy. This study used quasi-experimental pretest-posttest design without control group with 17 respondents and recruited by purposive sampling methode. Data were collected from patients with peripheral diabetic neuropathy and had 8 maximum score of foot sensitivity.. Foot sensitivity was measured on the 1st day of intervention and end day of intervention. Wilcoxon test analysis showed significant differences on foot sensitivity with combination of diabetic legs exercise and SPA therapy compare to diabetic legs exercise only (p value < 0.05). It can be inferred that combination of diabetic legs exercise and SPA therapy are more effective to increase legs sensitivity. Therefore, combined effect of those therapies may eventually decrease diabetic ulcers risk.